Effectiveness of fractionated carbon ion treatments in three rat prostate tumors differing in growth rate, differentiation and hypoxia - Glowa, Christin; Peschke, Peter; Brons, Stephan; Debus, Jürgen; Karger, Christian (Radiotherapy and oncology, 2021)
Purpose - To quantify the fractionation dependence of carbon (12C) ions and photons in three rat prostate carcinomas differing in growth rate, differentiation and hypoxia. - Material and methods - Three sublines (AT1, HI, H) of syngeneic rat prostate tumors (R3327) were treated with six fractions of either 12C-ions or 6 MV photons. Dose-response curves were determined for the endpoint local tumor control within 300 days. The doses at 50% control probability (TCD50) and the relative biological effectiveness (RBE) of 12C-ions were calculated and compared with the values from single and split dose studies. - Results - Experimental findings for the three tumor sublines revealed (i) a comparably increased RBE (2.47-2.67), (ii) a much smaller variation of the radiation response for 12C-ions (TCD50: 35.8-43.7 Gy) than for photons (TCD50: 91.3-116.6 Gy), (iii) similarly steep (AT1) or steeper (HI, H) dose-response curves for 12C-ions than for photons, (iv) a larger fractionation effect for photons than for 12C-ions, and (v) a steeper increase of the RBE with decreasing fractional dose for the well-differentiated H- than for the less-differentiated HI- and AT1-tumors, reflected by (vi) the smallest α/β-value for H-tumors after photon irradiation. - Conclusion - 12C-ions reduce the radiation response heterogeneity between the three tumor sublines as well as within each subline relative to photon treatments, independently of fractionation. The dose dependence of the RBE varies between tumors of different histology. The results support the use of hypofractionated carbon ion treatments in radioresistant tumors.
Gesehen am 22.06.2021